INVESTIGATION OF THE DAMPING CONSTANT OF FRAUNHOFER’S LINES IN SOLAR ATMOSPHERE - Yankiv-Vitkovska, L. (Одеські астрономічні публікації, 2017)
To define chemical contents of elements in stars’ atmospheres we need reliable data on their damping in spectral lines. We have found distinct expressions for damping constant with consideration of several mechanisms that in the expansion of spectral lines. We have calculated parameter of damping for some spectral lines under different temperatures with consideration of inelastic collisions by means of these expressions. Using the most correct and empirically tested method of investigation of spectral lines we have calculated parameter of damping for spectral lines of iron group in Solar atmosphere. Calculation of Damping Constant of Fraunhofer’s Lines in Solar Atmosphere.